2011
DOI: 10.1186/cc10558
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary resuscitation traumatic cardiac arrest - there are survivors. An analysis of two national emergency registries

Abstract: IntroductionCardiac arrest following trauma occurs infrequently compared with cardiac aetiology. Within the German Resuscitation Registry a traumatic cause is documented in about 3% of cardiac arrest patients. Regarding the national Trauma Registry, only a few of these trauma patients with cardiac arrest survive. The aim of the present study was to analyze the outcome of cardiopulmonary resuscitation (CPR) after traumatic cardiac arrest by combining data from two different large national registries in Germany.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 20 publications
3
35
1
5
Order By: Relevance
“…These predictors include the presence of bystander CPR and the arrest being witnessed by a bystander or EMS, both of which we showed to have no association with outcomes from traumatic OHCA. While bystander CPR rates in our region were higher than have been previously reported for traumatic OHCA,4 the utility of bystander CPR in traumatic cardiac arrest has been questioned7 19 and our results demonstrated that the presence of bystander CPR was not associated with achieving ROSC or survival to hospital in multivariable models. The presence of bystander CPR may also increase the likelihood of a paramedic attempting resuscitation in cases that are potentially futile.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…These predictors include the presence of bystander CPR and the arrest being witnessed by a bystander or EMS, both of which we showed to have no association with outcomes from traumatic OHCA. While bystander CPR rates in our region were higher than have been previously reported for traumatic OHCA,4 the utility of bystander CPR in traumatic cardiac arrest has been questioned7 19 and our results demonstrated that the presence of bystander CPR was not associated with achieving ROSC or survival to hospital in multivariable models. The presence of bystander CPR may also increase the likelihood of a paramedic attempting resuscitation in cases that are potentially futile.…”
Section: Discussioncontrasting
confidence: 70%
“…Previous studies have used descriptive statistics to characterise a cohort of traumatic OHCA patients that survived to hospital4 or hospital discharge,13 or compared survivors and non-survivors 3. Pickens et al 5 noted no differences in demographics and the mechanism of injury between survivors and non-survivors.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report by Gräsner and colleagues analysed German registry data, which included 1903 patients with trauma and cardiac arrest at the scene where CPR was performed 16. This report demonstrated that 25% of the patients had a return of spontaneous heart rhythm on arrival to the hospital.…”
Section: Resultsmentioning
confidence: 99%
“…Different EMS organisations may explain in part the discordant survival rates for TCA between recent studies5 6 and studies from the USA 14 15. Data, such as those presented here, emanate from a physician-staffed EMS and show a better prognosis 5 6.…”
Section: Discussionmentioning
confidence: 58%